CERTAIN PROBLEMS OF IMPLEMENTATION OF THE RIGHT OF NON-GOVERNMENTAL ORGANIZATIONS TO APPEAL TO ADMINISTRATIVE COURT - Siradeghyan, Tatevik (State and Law, 2024)
In the article entitled "Some problems of realization of the right of non-governmental organizations to appeal to administrative court", the issues of mechanisms of filing a lawsuit by non-governmental organizations within the framework of the institute of protection of others’ interests are discussed, based on the principles of accessibility of justice. The paper considers the role of non-governmental organizations in general and in particular in the field of initiating a lawsuit to protect the rights of others, presents the scientific and practical bases of the institute of protecting the rights of others in civil and administrative proceedings, the peculiarities of administrative justice, the norms of domestic legal norms, including the special procedure of considering the cases initiated by non-governmental organizations in accordance with Chapter 29.3 of the RA Code of Administrative Procedure. The scientific work is based on both theoretical and practical research; the problems of the institute of filing a lawsuit by non-governmental organizations to protect the rights of others are presented by studying the opinions of various authors, current legal norms, international and judicial bodies, experience of other countries; the author brings forward the need for their solution, reviews the existing legal norms, proposes ways to improve the legislation.